Skeletal Muscle Metastasis From Renal Cell Carcinoma: A Case Series and Literature Review - Sun, Juan; Zhang, Zimu; Xiao, Yu; Li, Hanzhong; Ji, Zhigang; Lian, Penghu; Zhang, Xuebin (Frontiers in Surgery, 2022)
Objectives Skeletal muscle metastasis (SMM) from renal cell carcinoma (RCC) has been rarely reported. This case series was performed to increase the clinicians' understanding of its clinical features and treatments. Methods We evaluated the clinical presentations, diagnoses, and treatments of 2 patients with SMM from RCC in our hospital and 39 cases reported in the literature. Results Among the 41 patients, 4 (9.76%) were women and 37 (90.24%) were all men. The average age was 60.5 ± 12.6 years old (range from 7 to 81). The size of tumors varied from 1 to 28 cm, and the metastatic sites of 6 (14.63%) cases were in the heads, 20 (48.78%) in the limbs, 9 (21.95%) in the trunks, 3 (7.32%) in the buttock, and the other 3 (7.32%) were multiple sites. The mean of intervals between the RCC and the discovery of the first SMM was 73.61 months. More than half of the patients (25, 60.98%) were diagnosed by MRI and 25 (60.98%) patients performed a biopsy of the mass to establish the diagnosis. Finally, 30 (73.17%) cases performed mass excision. Then the adjuvant therapy was performed in 18 patients including immunotherapy, radiotherapy, chemotherapy, and targeted therapy. The median follow-up after SMM was 9 months (P25, P75: 5, 23), in which the longest survival time of patients with SMM of RCC was 8 years while the shortest was only 3 months. Conclusion The characteristic clinical feature of SMM from RCC is asymptomatic masses or swelling with a long history which can be preoperative suspiciously diagnosed by MRI. The rapid biopsy of suspected lesions, determination of other metastasis sites, resection of metastasis, and systematic treatment are the recommended treatments of it.